2021
DOI: 10.3390/su13094688
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Asymmetric Impact of COVID-19 Pandemic and Global Financial Crisis on Dow Jones and Oil Price Shock

Abstract: COVID-19 has significantly affected the financial and commodity markets. The purpose of this investigation is to understand the impact of the COVID-19 crisis on Dow Jones and West Texas Intermediate (WTI) oil returns in relation to other crises using the Exponential Generalized Autoregressive Conditional Heteroskedasticity (EGARCH) model. The results indicate that COVID-19 and the accompanying lockdown have adversely impacted both yields and that the impact on oil prices is more significant than on the Dow Jon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…For example, workplace closure and domestic travel limitations positively impact global energy returns, while cancellation of public events and public transport closures impose a negative effect. Shehzad et al (2021) compare the impact of COVID-19 on oil prices and the Dow Jones index in terms of returns and volatility. The negative impact is higher in magnitude on oil prices compared to the Dow Jones index.…”
Section: Covid-19 and The Stock Returns Of Energy Companiesmentioning
confidence: 99%
“…For example, workplace closure and domestic travel limitations positively impact global energy returns, while cancellation of public events and public transport closures impose a negative effect. Shehzad et al (2021) compare the impact of COVID-19 on oil prices and the Dow Jones index in terms of returns and volatility. The negative impact is higher in magnitude on oil prices compared to the Dow Jones index.…”
Section: Covid-19 and The Stock Returns Of Energy Companiesmentioning
confidence: 99%
“…( Zhang and Hamori, 2021 ) revealed that the crude costs are accessible at everyday incidence. The preexisting research on exchange rate prediction applies every four weeks and every three months because macro market forces such as changes in prices of goods and services plus gross domestic product are solely accessible at these reduced incidences( Shehzad et al, 2021 ). ( Chatziantoniou et al, 2021a , Chatziantoniou et al, 2021b ) they proposed that the exchange rate forecastability significantly stayed at similar levels every four weeks and three months of incidence.…”
Section: Introductionmentioning
confidence: 99%
“…In the oil market, VaR can be used to quantify the maximum oil price change associated with a certain confidence level. The VaR of the oil market has increased more during the COVID-19 era than during the Global Financial Crisis [42], therefore we can expect that traditional statistical methods of risk measurement may not be appropriate to capture the risk with high accuracy. We assess how much the OVX can improve the VaR forecasts computed with the use of the statistical model.…”
Section: Introductionmentioning
confidence: 99%